Unveiling Islam: An Insider's Look at Muslim Life and Beliefs by Ergun Mehmet Caner and Emir Fethi Caner (Grand Rapids, Ml: KregeL Publications???? 2002. 256 pages.) (American Journal of Islam and Society, 2003)
Many books have been written on Muslims and Islam since 9/1 I. Amajority of them have tried to show Islam's negative side in an attempt toprove that Islam teaches violence and that Muslims love to engage injihad to become martyrs. Such contentions are generally made by antiMusliminterest groups, certain religious organizations, and politiciansunder the influence of such extremists. These people stir up anti-Muslimsentiments to influence public opinion and bend government policies infavor of such groups. This book is a similar attempt to gain popularity forthe authors and arouse anti-Muslim sentiment at a time that is trying formost Americans. The authors, Ergun Caner and Emir Caner, are brothers.The senior author is professor of theology at Criswell College, Dallas,Texas, and the second author teaches at the Baptist Seminary in WakeForest, North Carolina.The book contains a preface and introduction, I 6 chapters on variousaspects of Islam, and four appendices, including an index to the Qur'anand a glossary of Arabic terms. The preface is a story of the clash ofculturesbetween the authors' Muslim (Turkish) father and Swedish mother,which resulted in a divorce when the Caner brothers were still veryyoung. The father had visitation rights and would take Ergun and Emir tothe Islamic Center in Columbus, Ohio, on weekends "to do the prayers,celebrate Ramadhan and read the Qur'an." This was the children's onlyexposure to Islam, until Ergun was I 5 and visited a church after his bestfriend invited him to do so. Ergun found the people at church warm and"didn't mock when he stumbled through the hymns." He joined thegospel ministry in 1982 and has since been preaching (against Islam) inorder "to bring salvation for 1.2 billion Muslims." Thus the title of thebook is itself deceiving, as it conveys that a practicing Muslim became aChristian, when, in fact, the authors actually became Christians in theirearly teens and had almost no education in Islam.It is appalling that the introductory chapter opens with a threat from"Shaikh" Osama bin Laden to the Americans and blessings for those whogave their lives to k.ill the 9/1 I victims. The authors portray bin Laden asa typical Muslim who is out to get all people who refuse to accept Islam ...